Attracting Profit Shifting or Fostering Innovation? On Patent Boxes and RD Subsidies - Andreas Haufler; Dirk Schindler (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Many countries have introduced patent box regimes in recent years, offering a reduced tax rate to businesses for their IP-related income. In this paper, we analyze the effects of patent box regimes when countries can simultaneously use patent boxes and R&D subsidies to promote innovation. We show that when countries set their tax policies non-cooperatively, innovation is fostered, at the margin, only by the R&D subsidy, whereas the patent box tax rate is targeted at attracting international profit shifting. In equilibrium, patent box regimes emerge endogenously under policy competition, but never under policy coordination. We also compare the competition for mobile patents with the competition for mobile R&D units and show that enforcing a nexus principle is likely to reduce the aggressiveness of patent box regimes.
Keywords: H25; H87; F23; 330; corporate taxation; profit shifting; patent boxes; R&D tax credits; tax competition